Refractive Error Findings in Students Who Failed School-based Vision Screening. (4th July 2022) - Guo, Xinxing; Nguyen, Angeline M.; Vongsachang, Hursuong; Kretz, Alyssa M.; Mukherjee, M. Rani; Neitzel, Amanda J.; Shakarchi, Ahmed F.; Friedman, David S.; Repka, Michael X.; Collins, Megan E.
ABSTRACT: Purpose: To report refractive error findings in Baltimore City schoolchildren who failed school-based vision screenings. Methods: In this cross-sectional analysis, students pre-kindergarten through 8 th grade who failed screenings during school years 2016–2019 received an eye examination, including non-cycloplegic autorefraction and visual acuity (VA) measurements. Refractive error was identified when there was at least: −0.50 diopter (D) spherical equivalent (SE) myopia, +0.50D SE hyperopia, 1.00D astigmatism, or 1.00D anisometropia in either eye. Generalized estimating equation models were used to identify factors associated with clinically significant refractive error, defined as decreased VA and more severe refractive error. Results: Of 7520 students who failed screening, 6627 (88%) were analyzed. Clinically significant refractive error and any refractive error were found in 2352 (35.5%) and 5952 (89.8%) students, respectively. Mild myopia (45%, −0.50 D to <-3.00 D SE) and low astigmatism (47%, 1.00 D to <3.00 D cylinder) were the most prevalent types of refractive error. Proportions of students with myopia increased with higher grade levels (Ptrend <0.001). Myopia and astigmatism were more common in black and Latinx. Risk factors for clinically significant refractive error included higher grades (odds ratios [OR] ranged from 1.30 to 2.19 compared with 1 st grade, P < .05) and Latinx ethnicity (OR = 1.31, 95%CI: 1.08–1.59). Conclusion: A Baltimore school-based vision program identified a substantial number of students with refractive error in a high-poverty urban community. Over 1/3 students who failed vision screening had clinically significant refractive error, with black and Latinx students at higher risk of having myopia and astigmatism.